Transformation groups of certain flat affine manifolds (2021)
In this paper we characterize the group of affine transformations of a flat affine simply connected manifold whose developing map is a diffeomorphism. This is proved by making use of some simple facts about homeomorphisms of R preserving open connected sets. We show some examples where the characterization is useful.